Dynamics of sympathetic nerve activity in patients with functional tricuspid regurgitation and its postinterventional progression. (3rd October 2022) - Ozturk, C; Ozkan, N; Vogelhuber, J; Nickenig, G; Weber, M U; Hammerstingl, C
Abstract: Background: Increased muscle sympathetic nerve activity (MSNA) is associated with poor prognosis in patients with chronic heart failure (CHF). The improving effect of interventional therapy of mitral regurgitation (MR) and aortic stenosis on MSNA in patients with CHF has been previously shown. Purpose: MSNA in patients with functional tricuspid regurgitation (FTR) has not been evaluated yet, and the effect of transcatheter tricuspid valve repair (TTTVR) on MSNA is unknown. Methods: We prospectively included 28 patients with ≥ severe FTR who underwent TTVR. All patients were followed up at the earliest 12 months after the procedure. Microneurography was performed to determine MSNA, as described previously. Tungsten needles (200 μm) were used to record multiunit postganglionic sympathetic activity from the nervus peroneus longus close to the caput fibuli. There are two MSNA-defining parameters – burst frequency (burst/min) and burst incidence (burst/beats). In 9 patients, it was possible to perform microneurography at follow-up. Results: 28 patients (80.7±5.2 years, 53.6% female) with symptomatic (100% NYHA≥ II) high-grade FTR (severe TR: 78.6%, massive TR: 14.3%, torrential TR 7.1%) were prospectively included. At baseline, we documented preserved left ventricular function with a LVEF of 57.7±10.9%, however impaired right ventricular function (TAPSE: 15.8±5.2 mm) with biatrial dilation (left atrial volume: 95.4±40.7 ml, right atrial area: 31.8±10.8 cm 2 . Baseline NT pro-BNP was 2659.3±2214.3pg/dl. There was no relevant MR at baseline (MR ≤ moderate). According to baseline microneurography, we found a significantly increased MSNA (incidence: 146.16±65.85 bursts/beats, frequency: 182.21±140.6 bursts/min). Furthermore, MSNA was significantly and negatively correlated with renal function at baseline (MSNA incidence r=−0.67, p=0.0001; MSNA frequency r=−0.40, p=0.034). On the other hand, the serum level of NT pro-BNP showed a positive and significant correlation with MSNA incidence (r=0.64, p=0.0004), however no relevant association with MSNA frequency (r=0.23, p=0.24). The procedural success was 96.4%. One procedure was interrupted due to irreducible TR. At FU, we found sustained TR reduction (81.4% TR Conclusion: We documented increased sympathetic nerve activity in patients with FTR. Renal function inversely correlates with all MSNA-defining parameters, and MSNA incidence shows a positive correlation with levels of NT-pro BNP. TTVR decreases MSNA, which might be regarded as an additional neurological pathway of postinterventional clinical improvements apart from intracardiac volume and pressure changes. Funding Acknowledgement: Type of funding sources: None.